Critical thinking skills of prospective chemistry teachers in chemistry learning with Ethno-Socio-Scientific issues integrated inquiry - Dewi, Ratna Kumala; Rahayu, Sri; Muntholib, Muntholib; Sumarni, Woro (Eclética Química, 2025)
This study aims to develop a valid and practical Ethno-SSI integrated inquiry strategy to improve the critical thinking skills of prospective chemistry teachers. The research method used is Plomp’s research and development model, with a convenience sampling technique obtained from a sample of 52 prospective chemistry education teachers at one of the universities in Indonesia. Data was collected through observation, a critical thinking test, and a questionnaire. Data analysis was carried out qualitatively and quantitatively. The results of strategy development obtained a new syntax called OETACA (orientation, exploration, transformation, argumentation, conclusion, and application) with a content validity score of 0.83 and construct 0.93. The results of improving critical thinking skills on a small scale get an N-Gain score of 0.7 in the high category supported by the perceptions of prospective chemistry teachers who strongly agree (43%) and agree (41%) to implement the Ethno-SSI integrated inquiry strategy in chemistry learning in the classroom.